The Strategic Importance of Oil in The Iraqi Economy and Its Future Outlook in Light of The Current and Expected Oil Prices for The Period (2010-2030) - AHMED RASHID AJRASH; OTHMAN AWAD MUHAMMED; Dr. Khattab Imran Saleh (Research Parks Publishers, 2023)
In light of the growing discovered oil reserves, Iraq has become a huge oil wealth estimated at about (145) billion barrels, which makes it possess the fourth largest oil reserves in the world after Saudi Arabia, Venezuela and Iran, but it is currently facing enormous economic, technical, political and social challenges that prevent it from achieving economic development. . And as long as Iraq depends to a large extent and mainly on oil, it can be said that it must be recognized for Iraq's actual need to inject investment into the Iraqi economy, especially the oil sector, in light of what this economy has been exposed to over more than forty years of massive depletion of its resources through the trilogy. (Destruction - looting - corruption) There is no doubt that oil production has a strong relationship with the reality of the Iraqi economy, as oil revenues represent about 95% of the total state revenues, and oil revenues are the main engine for achieving Iraq's development and reconstruction. The research will also deal with an analysis of the reality of the Iraqi oil sector at the present time and in the future in order to present a future vision for reforming that sector, which represents the main source of funds necessary for reforming and developing the infrastructure of the oil sector. As well as the rest of the economic sectors The imbalance in the oil industries is due to internal and external challenges, and political factors are among the most important issues that affect weak investment in the sector and its development. All of the foregoing stems from the nature of the relationship between new oil discoveries, oil investments, oil production, oil revenues, reconstruction and development. For this reason, the tightness of the relationship for this subject is discussed in the light of different oil prices